Monolithic InP‐based coherent transmitter photonic integrated circuit with 2.25 Tbit/s capacity. Issue 16 (1st July 2014) - Summers, J.; Vallaitis, T.; Evans, P.; Ziari, M.; Studenkov, P.; Fisher, M.; Sena, J.; James, A.; Corzine, S.; Pavinski, D.; Ou‐Yang, J.; Missey, M.; et al.
Abstract : A monolithic dual‐polarisation quadrature phase shift keying transmitter is demonstrated for operation at 2.25 Tbit/s over 40 wavelengths and 1 THz of spectral bandwidth. The single‐chip InP‐based transmitter employs 40 tunable distributed feedback lasers, 80 nested Mach‐Zehnder modulators and other elements to provide more than 1700 integrated photonic functions.